Gynostemma pentaphyllum: A review on its traditional uses, phytochemistry and pharmacology - Xiujuan Li; Lun Liu; Song Wei (Journal of Functional Foods)
Gynostemma pentaphyllum (GP), recognized as both an edible vegetable and health tea, has been consumed for thousands of years. Chemical research indicates GP primarily contains active ingredients including saponins, polysaccharides, and flavonoids. Notably, saponins and polysaccharides are among the main active components of GP, which have been extensively utilized in medicine, food, healthcare, and cosmetics due to their bioactivities including anti-tumor, anti-oxidation, hypoglycemic, cardioprotective, neuroprotective and anti-inflammatory activities. We conducted searches in various online databases, including Elsevier, Springer, PubMed, Web of Science, and China Knowledge Network (CNKI), to gather literature on the traditional uses, structural characteristics, and biological activities of the active ingredients of GP published prior to October 2024. In this review, GP saponins were categorized and GP polysaccharides discovered in the last ten years were highlighted. Then, the bioactivities of GP are summarized and lays a solid foundation for its development as a functional health food.